The interdisciplinary training team cooperation in China table tennis team - Qin, Z.; Zheng, X.; Xiao, D. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
For a long time, the Chinese table tennis team has made brilliant achievements in the world table tennis. It is a typical representative of the Chinese athletics team and a proud of Chinese people. Behind the gold medal are a scientific training, system management and integration of all resources creatively. Ahead of other sports, the Chinese table tennis team has already raised the concept of compound training team. In the continuous practice and constant innovation of this training mode, it has been proved as an effective organization form, and contains the profound connotation and speculative. Method: Through the literature material method, interview method, logical analysis, case analysis and other research method, this article summarizes and refines the effect and experience of the using of compound training cooperation. The study was aimed to enrich table tennis theory system, as well as to provide practical reference to other competitive sports team. Results and conclusions: 1 The goal of the Chinese table tennis team: maintaining the leading position of world table tennis, getting good mark in the Olympic Games and other international competition, and winning honour for our country. 2 Agency branch and system: the manager responsibility system. It is made up of team committee, head coach, men's and womenfs head coach, the leader of a group, the coaching staff and scientific research personnel, medical personnel and the directors. 3 The core and main body of compound training team cooperation of Chinese table tennis team is coaching team and the scientific research team. In the cooperation, the coaching team and scientific research team do work with each other, not in isolation. Chief coach is both the leader of coaching team and the participant of research team, a junction of team operation. 4 The organization management mode is scientific and reasonable: with advanced management concept; reasonable organization and management agencies; brainstorm decision concept; perfect management system and strict discipline. 5 Following the principle of training, scientific training and development is an important assurance for the Chinese table tennis to keep long time situation for a long time. 6 Having the highest goal of the motherland, no failure only success became the motivation of the team members to the relentless pursuit. The spirit of patriotism is the mainstream of the team all along, the mainstay to support the team. 7 Cycle practice of London Olympic Games shows: as to compound training team construction of gtraining, science, medical and protecth, the Chinese table tennis team has accumulated valuable wealth, and its operation mechanism and mode of cooperation is worthy of reference for our country's other competitive project team to learn.